2016
DOI: 10.1007/978-3-319-33943-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Thyroid Hormones on Tendon Homeostasis

Abstract: Tendinopathies have a multifactorial etiology driven by extrinsic and intrinsic factors. Recent studies have elucidated the importance of thyroid hormones in the alteration of tendons homeostasis and in the failure of tendon healing after injury. The effects of thyroid hormones are mediated by receptors (TR)-α and -β that seem to be ubiquitous. In particular, T3 and T4 play an antiapoptotic role on tenocytes, causing an increase in vital tenocytes isolated from tendons in vitro and a reduction of apoptotic one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…Moreover, thyroid hormones are major determinants of tissue function, playing well-defined roles in cell signaling. The role of thyroid hormones in tenocyte physiology is a novel area of study in this field [14, 15, 40, 41]. Moreover, THs regulate the function of stem cells, controlling self-renewal, proliferation, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thyroid hormones are major determinants of tissue function, playing well-defined roles in cell signaling. The role of thyroid hormones in tenocyte physiology is a novel area of study in this field [14, 15, 40, 41]. Moreover, THs regulate the function of stem cells, controlling self-renewal, proliferation, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous reports have shown that tendons express thyroid hormone (TH) receptor isoforms and that T 3 and T 4 hormones enhance tenocyte proliferation in vitro [14, 15]. Moreover, T 3 and T 4 contrast apoptosis in healthy tenocytes in a dose- and time-dependent manner [14, 15]. THs (especially T 3 ) stimulate cellular proliferation and type I collagen formation, the major fibrillar collagen in tendons.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies showed that insertional Achilles CT is generated by a process similar to endochondral ossification, and it has a structure similar to trabecular bone 12 . In this process, resident MSCs and their erroneous differentiation into osteoblasts may play an important role 5 . Several studies discussed the adverse effects of MSCs in pathogenic conditions, including vascular calcification 13 , aortic valve calcification 14 , fibrodysplasia ossificans progressive 11 .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence about the influence of hormones and metabolic diseases, like hypothyroidism, obesity and diabetes mellitus, on tendons homeostasis [5][6][7] . More than 30% of patients with insulin-dependent diabetes have tendon calcifications.…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%
“…The structure and the function of the tendons could be impaired by several systemic metabolic, genetic and neurological diseases, such as diabetes (Batista et al, 2008), endocrinological disfunctions (hypothyroidism) (Oliva et al, 2016), genetic enzymatic defect and spasticity .…”
Section: Introductionmentioning
confidence: 99%